Historical and recent shore erosion along the Colombian Caribbean Coast (2005)
The analysis of historical charts, aerial photographs, satellite images and fieldwork provides a general picture of the magnitudes, rates and some of the possible causes of the main shoreline changes occurred along the littoral since 1794 until present. Net littoral accretion took place mostly on localized deltaic zones, but cliff and beach retreat has been by far the dominant trend in this coast, particularly along the coastline to the south of Sierra Nevada de Santa Marta. Data concerning the Guajira Peninsula and Sierra Nevada de Santa Marta shores suggest a coastline retreat of 20-30 m in the last century, while for the southern Caribbean, between the Magdalena delta and the Gulf of Urabá, accurate charts of XVIII-XIX centuries evidence littoral retreat up to 12 km and maximum rates of erosion up to 40 myr-1 at some areas. Shore erosion and consequent flooding along the Caribbean coast of Colombia had induced important land losses, both in non-developed and developed areas, and is impacting severely the infrastructure of all the inhabited littoral sectors. Available data for the most critical areas demonstrates that natural instability and/or pre-existing erosive trends are facilitated by soft lithologies and were dramatically accelerated in the last eight decades by intensive human interventions, including the chaotic building up of hard rock coastal defenses, the diversion of low river courses and the intensive beach and river sand extraction.